Risk assessment for type 2 diabetes mellitus in a clinic western Paraná (Research, Society and Development, 2021)
Diabetes mellitus is a serious public health problem which the early detection and treatment are extremely important to reduce the morbimortality rates. This study aims to evaluate the prevalence of individuals with possible prediabetes and high risk for type 2 diabetes mellitus in patients and companions at a clinic in western Paraná. A questionnaire adapted from American Diabetes Association was conducted to estimate the risk score in 223 participants. 38.2% of patients without diagnosis of diabetes presented a high risk for the disease. Statistically significant risk factors were: advanced age, positive family history, hypertension and increased mass index. The study concluded that a large part of the sample is at increased risk for type 2 diabetes and is likely to have prediabetes. The use of practical and effective tools such as the American Diabetes Association risk questionnaire may benefit public health policies.